OPTIMALISASI ZAKAT DALAM EKONOMI ISLAM (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2016)
As a pillar of Islam, zakat is the economic foundation of moslems. The distributionof zakat for productive activities has certainly brought positive impacts on thenational development. Also, zakat has been the main capital of the lower economicsociety. In the Islamic economic discussion, zakat promotes the justice valuesfocusing on the micro economy. As the social instrument, zakat plays an importantrole in the moral and social-based economic development. As Mannan points outthat zakat is built upon the five principles namely faith, productivity, logicalreasoning, easiness, and truth. This writing reveals the role of zakat in the historyand its contribution for ritual worship as well as the moslem’s prosperity,particularly for the mustahiq, those who receive the zakat.The question remains is whether zakat is believed as the asset of socio-economicgrowth or as a mere Islamic ritual. Another question is about the management ofzakat which should be productive rather than consumptive. This writing deals withthe discussion of zakat as an Islamic ritual which is inherent with socio-economiccontext. This writing uses the comparative approach between normative principles(al-Qur’an and Hadits) and its socio historical implication.